IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SEJARAH PADA KURIKULUM 2013 DI SMA NEGERI 1 BOYOLALI - Jati, Bayu Prasetyo; W., Wasino; Mursadad, Akhmad Arif (Sebelas Maret University (UNS), 2015)
This research aims (1) to understand and analyze the socialization process of the curriculum 2013 on the history teachers in SMA Negeri 1 Boyolali; (2) to explain the implementation of the curriculum 2013 in the history learning with the scientific approach in SMA Negeri 1 Boyolali; (3) to explain the implementation of education character through the history lesson SMA Negeri 1 Boyolali; (4) to examine the impact of history learning on the increased character of students; ( 5 ) to explain the obstacles and efforts of the teachers in the implementation of the history learning in the curriculum of 2013 in SMA Negeri 1 Boyolali.The method used in this research is descriptive qualitative. It is said as descriptive qualitative study since it puts more emphasis on the process. This form will be able to capture the various descriptive qualitative information with a meticulous and full of nuances that are more valuable than a mere statement of amount or frequency in the form of figures. Strategy used is a case study, where the researcher has to gather data completely and precisely of the case to know everything that is hidden from the problems researched.The results of the research show that (1) in the socialization process of the curriculum 2013 in SMA Negeri 1 Boyolali, all the history teachers has followed training. The training was held by the Institute of Development and Empowerment of the School Principal (LPPKS); (2) the teachers have run history learning with the scientific approach with Problem Learning Base model; (3) the implementation of education character through the history lesson runs well, the teachers always input character values in the history learning. The values which are in the material that are taught by the teachers of class X IIS 1 and XI MIA 4 namely the religious value, honest value, hard work value, creative value (think logically, and critically), independent value, democratic value, nationality spirit value, the love of homeland value, and the responsibility value; (4) In the history learning that has been implemented by the teachers, the impact on the increased character do not directly come up with a sudden or instant. The simple impact is the students are pleased and interested with the history lesson, when the teachers explain material and conduct a discussion, the students are enthusiastic; (5) In the implementation of hstory learning in SMA Negeri 1 Boyolali, there are obstacles found. The obstacles are found in the learning device which are many and complicated, the Learning Design Plan (RPP) and the assessment. Besides is the lack of the material in the history learning book in curriculum 2013. The effort that has been done, the teachers are disciplined in making the planning (RPP) or assessment, and to overcome the lack of material, the teachers direct the students to collect information from various sources.Â